2010
DOI: 10.1007/s11999-009-0990-8
|View full text |Cite
|
Sign up to set email alerts
|

Does an Arthroscopic Suture Bridge Technique Maintain Repair Integrity?: A Serial Evaluation by Ultrasonography

Abstract: Level IV, therapeutic study. See Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
80
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(83 citation statements)
references
References 34 publications
1
80
2
Order By: Relevance
“…1 Although the clinical impact of rotator cuff retears remains a point of controversy in the literature, [2][3][4][5] several studies have shown that retears affect functional recovery. [6][7][8][9] Several patient-related risk factors associated with retear have been identified. These include age, [10][11][12][13] preoperative tear size, 7,14-16 muscle atrophy, 14,17 and other factors.…”
mentioning
confidence: 99%
“…1 Although the clinical impact of rotator cuff retears remains a point of controversy in the literature, [2][3][4][5] several studies have shown that retears affect functional recovery. [6][7][8][9] Several patient-related risk factors associated with retear have been identified. These include age, [10][11][12][13] preoperative tear size, 7,14-16 muscle atrophy, 14,17 and other factors.…”
mentioning
confidence: 99%
“…Serial evaluation with ultrasonography might be a good alternative. 20) One recent study reported that all retears occurred prior to 6 months after surgery in serial ultrasound follow-up up to 24 months, with a 41% retear rate. 9) Another author also reported a high frequency of retear within the first 6 months (75.0% [6 of 8]), justifying the evaluation at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…18) Recent suture bridge technique had generally reduced the retear rate compared with more conventional technique. 4,6,8,9,19,20) Many authors reported the retear rate from 8%…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Some authors have reported that arthroscopic repairs of full-thickness rotator cuff tears (FTRCTs) are associated with improved functional scores and a 71% to 91% healing rate. 3,16,26,28 A number of reports specifically focus on partial-thickness rotator cuff tears (PTRCTs), 4,7,10,14,29,33,36,40 which can be classified as bursal, articular, or intratendinous based on their location. The partial articular-side supraspinatus tendon avulsion (PASTA) lesion 32 is a well-known articular-side PTRCT, and a new arthroscopic transtendon cuff repair technique was developed to treat PASTA lesions in relatively young and active patients whose lesions had not converted to full-thickness cuff tears.…”
mentioning
confidence: 99%